2017
DOI: 10.1177/1060028017736539
|View full text |Cite
|
Sign up to set email alerts
|

The ABCs of Immunotherapy for Adult Patients With B-Cell Acute Lymphoblastic Leukemia

Abstract: Outcomes of patients with relapsed disease are improving thanks to new therapies such as blinatumomab, inotuzumab, and CAR T-cells. Although the efficacy of these therapies is impressive, they are not without toxicity, both physical and financial. The optimal sequencing of these therapies still remains a question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
(82 reference statements)
0
9
0
Order By: Relevance
“…Phase I/II and III trials have shown promising results with high numbers of patients achieving minimal residual disease negative status and impressive rates of complete remission [3,8,9]. High response rates allow more patients to proceed to HSCT [9], it is better than standard salvage chemotherapy in R/R patients, and has efficacy when used in combination with low-dose chemotherapy for older adults with newly diagnosed ALL (NCT0371630) [10] but without additional toxicity. A concern with inotuzumab ozogamicin has been the incidence of veno-occlusive disease [8][9][10] and liverrelated toxicities [7,9,10] that can be ameliorated by careful patient management.…”
Section: Inotuzumab Ozogamicinmentioning
confidence: 99%
See 3 more Smart Citations
“…Phase I/II and III trials have shown promising results with high numbers of patients achieving minimal residual disease negative status and impressive rates of complete remission [3,8,9]. High response rates allow more patients to proceed to HSCT [9], it is better than standard salvage chemotherapy in R/R patients, and has efficacy when used in combination with low-dose chemotherapy for older adults with newly diagnosed ALL (NCT0371630) [10] but without additional toxicity. A concern with inotuzumab ozogamicin has been the incidence of veno-occlusive disease [8][9][10] and liverrelated toxicities [7,9,10] that can be ameliorated by careful patient management.…”
Section: Inotuzumab Ozogamicinmentioning
confidence: 99%
“…High response rates allow more patients to proceed to HSCT [9], it is better than standard salvage chemotherapy in R/R patients, and has efficacy when used in combination with low-dose chemotherapy for older adults with newly diagnosed ALL (NCT0371630) [10] but without additional toxicity. A concern with inotuzumab ozogamicin has been the incidence of veno-occlusive disease [8][9][10] and liverrelated toxicities [7,9,10] that can be ameliorated by careful patient management. However, the safety analysis showed that patients treated with inotuzumab ozogamicin had less thrombocytopenia and less febrile neutropenia than those on standard therapy [9].…”
Section: Inotuzumab Ozogamicinmentioning
confidence: 99%
See 2 more Smart Citations
“…Blinatumomab, a novel agent approved for relapsed or refractory B-cell ALL was not available at the time of this cohort analysis and could potentially reduce the number of patients needing anti-CD19 CAR-T cells. 21 Results have been promising with complete remission with blinatumomab of 30-45% of patients, but it remains unclear how durable these remissions will be. 22,23 Second, inotuzumab ozogomycin was also not available at the time of this analysis but is another therapy with promising results in ALL.…”
mentioning
confidence: 99%